2022
DOI: 10.1021/acscatal.2c01286
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Chemical Catalysis for Plastic Recycling

Abstract: Plastics are indispensable, but their pollution is triggering a global environmental crisis. Although many end-of-life catalytic options have involved converting plastics into valuable products, a deep understanding of the relationship between polymer structure and recycling performance is significant and urgently needed. Here, we start with a primer of polymeric chain structures on chemical recycling and discuss the structure–performance relationship between the polymer, catalyst, and catalytic reaction. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
102
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(105 citation statements)
references
References 141 publications
0
102
0
3
Order By: Relevance
“…최근 연구에 따르면 폐플라스틱의 매립 (landfilling, 40%)과 소각 (incineration, 27%)는 적은 폐플라스틱 처리비용이 탓에 현재 가장 널리 사용되고 있다 [5] . 폐플 eq emission index를 가지고 있다 [6] . 폐플라스틱 매립 은 분해에 오랜 시간 (50-600년)이 걸리는 플라스틱의 특성 탓에 지속적으로 매립할 장소가 필요하며, 독성과 유해물질이 토양과 지하수에 스며들 수 있기에 자원 순 환적 (circular)적인 폐플라스틱 처리방식이 아니다.…”
Section: 폐플라스틱 재활용 방식unclassified
See 3 more Smart Citations
“…최근 연구에 따르면 폐플라스틱의 매립 (landfilling, 40%)과 소각 (incineration, 27%)는 적은 폐플라스틱 처리비용이 탓에 현재 가장 널리 사용되고 있다 [5] . 폐플 eq emission index를 가지고 있다 [6] . 폐플라스틱 매립 은 분해에 오랜 시간 (50-600년)이 걸리는 플라스틱의 특성 탓에 지속적으로 매립할 장소가 필요하며, 독성과 유해물질이 토양과 지하수에 스며들 수 있기에 자원 순 환적 (circular)적인 폐플라스틱 처리방식이 아니다.…”
Section: 폐플라스틱 재활용 방식unclassified
“…폐플라스틱 매립 은 분해에 오랜 시간 (50-600년)이 걸리는 플라스틱의 특성 탓에 지속적으로 매립할 장소가 필요하며, 독성과 유해물질이 토양과 지하수에 스며들 수 있기에 자원 순 환적 (circular)적인 폐플라스틱 처리방식이 아니다. 또 한, 그림 3에서 볼 수 있듯, 순환적이지 않은 방식이기 에 CO 2 -eq emission index가 소각 방식 다음으로 높은 것을 확인할 수 있다 [6] . Adapted with permission from ref [6] 노인수 특 집 하는 방식이다 [7][8][9][10][11][12][13] .…”
Section: 폐플라스틱 재활용 방식unclassified
See 2 more Smart Citations
“…15 A review of catalytic systems for PET degradation has recently been reported. 16 Research on the transesterification of polyester for degradation has become a significant research focus. The importance to this approach is the catalyst.…”
mentioning
confidence: 99%